Literature Review : The Effect of Capital Structure on Firm Value in Publicly Listed Companies in Indonesia - Romida Br Sibarani; Sherly Marlinda Hutabarat; Handriyani Dwilita (International Forum of Researchers and Lecturers, 2025)
This study examines the influence of financial structure on enterprise value in consumer-focused firms registered on the Indonesia Stock Exchange. Financial structure, characterized as the proportion of borrowing and equity, plays a significant role in financial management, shaping both business performance and market perception. Utilizing a qualitative method through a literature review, this research gathers and analyzes various sources to evaluate the connection between financial structure and enterprise value. The findings indicate that financial structure can have both positive and negative impacts on enterprise value. Integrating borrowing into the financial structure offers benefits such as tax advantages, enhanced profitability, and a favorable signal to investors. However, excessive reliance on borrowing can result in increased financial burdens, such as higher interest expenses, which may lower enterprise value. These results underscore the importance of maintaining an appropriate debt-to-equity ratio to improve or sustain enterprise value.